Integrating environmental management practices with strategic planning process. - Chong, Stephanie Wing Hin Oy Nee. (2008)
Integrating environmental issues into strategic planning: developing a self-assessment tool. This project studies the environmental practices of the ISO 14001 certified companies in Singapore and examine the extent to which such practices are integrated with the corporate strategy.